PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA HOTEL MUTIARA DI RANGKASBITUNG - Euis Ajizah; Siti Nurlaela (Universitas La Tansa Mashiro, 2018)
The results of the study show that service quality has a significant effect on customer satisfaction at the pearl hotel in Rangkasbitung. As evidenced by simple linear regression equation Y = 34,929 + 0,234 X and R square of 0,061 which means 6,1% customer satisfaction is influenced by variable service quality variables, and the significance is seen from t count> t table (2,534> 1,984) with significant 0,013> 0 , 05. Which means if tcount <t table, then H0 is accepted and H1 is rejected. This means that there is no influence between service quality (X) on consumer satisfaction (Y) and if thitung> t table then H0 is rejected and H1 is accepted. This means that there is an influence of service quality (X) on customer satisfaction (Y).